Microbial diversity and metabolomics analysis of colon contents exposed to cadmium and polystyrene microplastics - Dechun Chen; Liyu Pan; Xuan Ran; Junyu Huang; Xiaohua Teng; Falong Yang; Haifeng Liu (Ecotoxicology and Environmental Safety)
Cadmium and microplastics, common pollutants, can accumulate in the body, impacting the intestinal barrier and harming livestock breeding. In order to explore the damage mechanism of cadmium and cadmium combined microplastic on the colon of mice, 60 mice were divided into three groups: The control group (0.2 mL of saline), cadmium group (Cd group, 0.2 mL of 4.8 mg/kg/d CdCl2) and mixed group (Mix group, 0.2 mL of mixed solution containing 4.8 mg/kg/d CdCl2 and 10.0 mg/d MPs) were fed for 42 d. The changes of colon histopathology were observed, and the changes of microbial diversity and metabolomics of colon contents were analyzed. Pathological sections of the colon showed abnormal mucosal hyperemia with mixed exposure compared to cadmium exposure. Microbial diversity analysis showed increased abundances of Enterococcus, Adlercreutzia, and Bifidobacterium in the Cd and Mix groups, with Dubosiella being the most significantly increased. Metabolomic analysis indicated significant differences in nucleotide and purine metabolism between the Cd and control groups, and in linoleic acid and bile acid metabolism between the Mix and control groups. The ABC transporter metabolites increased with Cd exposure, while the PPAR pathway metabolites were enriched with MPs exposure. Correlation analysis highlighted several key findings: Pasteurella exhibited a notably negative association with pantothenate. Conversely, Enterococcus demonstrated a significant positive link with palmitoylcarnitine. Additionally, both Adlercreutzia and norank_f_Eggerthellaceae showed a positive correlation with azelaic acid. These findings suggest that Cd and MPs disrupt intestinal microbiota and metabolic pathways, providing insights into potential treatments for such exposures.